BIOCHEMICAL AND BIOINFORMATICS ANALYSIS OF TWO (rumus)-AMYLASES FROM Bacillus megaterium NL3 - SITI SHOFIYAH , SOFI
(rumus)-Amylase (EC 3.2.1.1) hydrolyzes (rumus)-1,4-glycosidic bonds of polysaccharides producing linear and branched oligosaccharides. Based on amino acid sequences, (rumus)-amylase is classified into the glycoside hydrolase 13 family (GH13). The GH13 (rumus)-amylases generally have a ((rumus)/(rumus))8-barrel catalytic domain structure, 4(rumus)7 conserved sequence regions (CSR), and three conserved catalytic residues, namely aspartate as a nucleophile, glutamate as a proton donor, and aspartate as a transition state stabilizer. (rumus)-Amylases are produced by various organisms. Bacillus megaterium NL3 is a bacterium associated with a sea anemone from the land-locked marine Lake Kakaban, Indonesia, which produces two type of (rumus)-amylases, namely BmaN1 and BmaN2. BmaN1 has different catalytic residues compared to the conserved catalytic residues of GH13. The first aspartate shifts i+1 from its conserved position (Asp203), the second aspartate is replaced by His294, while glutamate (Glu231) is identical to the conserved catalytic residue. The second (rumus)-amylase, BmaN2, has general three catalytic residues, namely Asp233, Glu273, Asp340, as found in GH13. The previous study showed that BmaN2 has raw starch degrading activity. The aims of this study were to investigate the role of residues located in the catalytic region in order to understand reaction mechanism catalyzed by BmaN1; to perform biochemical analysis of BmaN2 in terms of the effect on several ions, a chelating agent, and kinetic parameters; and to analyze residues responsible for starch binding. BmaN1 was produced in Escherichia coli BL21(DE3) as an inclusion body. An active BmaN1 wild type (WT) was obtained by refolding using urea gradient from 8 M to 0 M. The refolded BmaN1 WT was then purified by the Ni-NTA affinity column chromatography. The purified BmaN1 had a specific activity of 20.9 U/mg towards soluble starch and an IC50 of 34.7 (rumus)M on acarbose. To determine the role of residues in the catalytic region of BmaN1, site-directed mutagenesis was performed on the codon encoding amino acid residues Glu231, His294, and Lys202 which lies one residue preceding the first catalytic aspartate (Asp203). The resulted mutants were designated as BmaN1 Glu231Gln, BmaN1 His294Asp, and BmaN1 Lys202Asp. Mutants BmaN1 were produced in E. coli BL21(DE3), then refolded and purified. BmaN1 Glu231Gln and BmaN1 His294Asp had lost 95% and 40%, respectively, while BmaN1 Lys202Asp showed no amylolytic activity. Based on the alignment of amino acid sequences among BmaN1 and other GH13 (rumus)-amylases and the crystal structure of (rumus)-amylase of Geobacillus thermoleovorans with acarbose (PDB code: 4E2O), Glu231 acts as a proton donor and His294 is predicted to replace the role of aspartate as a transition state stabilizer. Substitution of Glu231Gln eliminated the ability of BmaN1 to protonate the glycosidic linkage, hence the catalysis reaction does not occur. Based on modeling studies, the partial loss of activity in the His294Asp substitution is due to the disruption of hydrogen bonds in the vicinity of His294. The Lys202Asp substitution leads to the environmental changes of Asp203, as predicted by the model structure. Hence, BmaN1 Lys202Asp lost its activity completely. BmaN2 was produced in E. coli ArcticExpress (DE3) as a soluble protein and purified by Ni-NTA affinity column chromatography. BmaN2 has a specific activity of 22.5 U/mg. It retained a minimum of 61% residual activity in 5 mM concentration of selected metal ions, Na+, Ba2+, Ni2+, Mn2+, Ca2+, and Mg2+. However, BmaN2 activity decrease dramatically in the presence of Pb2+ and Zn2+. The addition of 10 mM EDTA reduced BmaN2 activity by 78%, suggesting that BmaN2 is a metal-dependent enzyme. The kinetic parameters, KM, Vmax, and kcat/KM of BmaN2 were 4.73(rumus)1.12 mg mL(rumus)1, 39.07(rumus)3.22 (rumus)g min(rumus)1, and 30.4 mL mg(rumus)1 min(rumus)1, respectively. Based on the alignment of amino acid sequences of GH13_36 and the model structure, BmaN2 consists of three domains, namely the catalytic domain A ((rumus)/(rumus))8-barrel, B domain, and C domain, but has no starch binding domain (SBD). Therefore, the ability of raw starch hydrolysis of BmaN2 might be due to the presence of particular residues, which is commonly named as substrate binding sites (SBS). Three residues were predicted as SBS, namely Tyr101, His141, and Trp179 which are conserved in GH13_36.